2023
DOI: 10.3390/toxics11040397
|View full text |Cite
|
Sign up to set email alerts
|

Tebuconazole Induces ER-Stress-Mediated Cell Death in Bovine Mammary Epithelial Cell Lines

Abstract: Tebuconazole (TEB) is a triazole fungicide used to increase crop production by controlling fungi, insects, and weeds. Despite their extensive use, people are concerned about the health risks associated with pesticides and fungicides. Numerous studies have defined the cellular toxicity of triazole groups in pesticides, but the mechanisms of TEB toxicity in bovine mammary gland epithelial cells (MAC-T cells) have not yet been studied. Damage to the mammary glands of dairy cows directly affects milk production. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…It also increased caspase 3/7 activity in three human cell lines (HepG2, HEK293 and JEG3) at a concentration of 50 ppm [41]; in rat kidney cells, caspase 3/7 was induced at 175-200 µg/L [44]; and propiconazole in zebrafish increased caspase 3/7 activity by 1 µg/L [45]. Likewise, studies such as ours also found that triazole fungicides are able to alter the gene expression of te cell death biomarkers BAX, BCL2, BNIP3, APAF1 and AKT1 [37,43,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It also increased caspase 3/7 activity in three human cell lines (HepG2, HEK293 and JEG3) at a concentration of 50 ppm [41]; in rat kidney cells, caspase 3/7 was induced at 175-200 µg/L [44]; and propiconazole in zebrafish increased caspase 3/7 activity by 1 µg/L [45]. Likewise, studies such as ours also found that triazole fungicides are able to alter the gene expression of te cell death biomarkers BAX, BCL2, BNIP3, APAF1 and AKT1 [37,43,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 66%
“…Epoxiconazole was able to induce caspase 3 activity in F98 glioma cells at a concentration of 12-50 µM [25,34], in PC12 cells at a concentration of 5-20 µM [33] and in neural stem cells at a concentration of 2-10 µM [24]; in three human cell lines (HepG2, HEK293 and JEG3), caspase 3/7 was induced at a concentration of 125 g/L [41]. Tebuconazole increased caspase 9 and caspase 3 activation in myocardial cells at doses of 0.9, 9 and 27 mg/kg b. w. [42]; in bovine mammary gland epithelial cells at 100-200 µM [43]; in HCT116 cells at increasing doses of 12. 5, 25, 50 and 75 µM [40]; and in cardiac cells at concentrations of 30 and 60 µM [10].…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, cDNA was synthesized using MMLV reverse transcriptase (Thermo Fisher Scientific, Waltham, MA, USA), with the cDNA serving as a template for qPCR. The qPCR procedure and data analysis methods were consistent with our previous study [74]. The specific qPCR primer sequences are provided in Table 1.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 81%
“…Beyond cancer, the beneficial effects of MitoQ on various diseases have been previously documented, including the inhibition of prostatic hyperplasia via androgen receptor and NOD-like receptor family pyrin domain-containing 3 inhibition [68][69][70][71][72][73][74]. Additionally, MitoQ has successfully completed phase I safety and phase II clinical trials for diverse diseases, including Parkinson's disease and hepatitis C. Numerous studies have demonstrated that MitoQ provides protection against oxidative stress-induced conditions in both cell lines and animal disease models [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation